Photo-induced reduction of Noble metal ions to metal nanoparticles on tubular J-aggregates - Stefan Kirstein; Hans von Berlepsch; Christoph Böttcher (International Journal of Photoenergy)
Palladium and silver nanoparticles are formed on the surface of tubular J-aggregates of an amphiphilic tetrachlorobenzimidacarbocyanine dye by reduction of the respective metal cations in aqueous solution. Upon addition of the palladium complex Na2PdCl4 to the aggregate solution, the absorption spectrum shows significant changes which is explained by partial destruction of the aggregates. Cryogenic transmission electron microscopy (cryo-TEM) images show that the tubular J-aggregates are randomly covered by well-separated Pd nanoparticles of approximately 1–3 nm size. Larger particles and higher particle density along the aggregates are obtained when an auxiliary reducing agent is added to the solution. The presence of the metallic particles leads to efficient fluorescence quenching giving clear evidence for super quenching. In similar experiments using AgNO3, silver nanoparticles are grown which are larger in size but less dense distributed along the aggregates. At least in the case of the silver particles, the spontaneous formation of metal nanoparticles is assumed to be initiated by a photo-induced electron transfer process (PET).